(untitled) (Revista Contexto & Saúde, 2026)
Parkinson’s disease (PD) remains an incurable condition, and strategies to mitigate oxidative stress and neurodegeneration have been widely investigated, including the use of plant-derived extracts and infusions rich in bioactive compounds, such as yerba mate (Ilex paraguariensis). Based on this premise, the present study evaluated the effects of an aqueous yerba mate extract in an in vitro model of PD. Differentiated SH-SY5Y cells exhibiting a neuronal phenotype were exposed to increasing concentrations of rotenone (5, 10, 40, and 100 µM), and the concentration that induced cytotoxicity after 24 h while maintaining 80–85% cell viability relative to the control was selected. Neuronal cultures were supplemented with aqueous yerba mate extract (0, 1, 5, 10, 20, and 100 µg/mL). The extract was characterized by the presence of alkaloids (caffeine and theobromine), tannins, and polyphenolic compounds. Treatment with yerba mate at 10 µg/mL in cultures exposed to 40 µM rotenone reduced cytotoxicity and apoptosis, as assessed by flow cytometry, and modulated the gene expression of antioxidant enzymes and the expression and protein levels of caspases-3 and -8. Although oxidative stress parameters in the yerba mate plus rotenone group remained higher than those observed in cultures treated with yerba mate alone, indicating partial attenuation of antioxidant effects in the presence of rotenone, protection against oxidative DNA damage was observed. Overall, these findings suggest that the aqueous yerba mate extract exerts modulatory effects on oxidative stress and cell death pathways in this in vitro model of PD.